Workplace gaslighting: Conceptualization, development, and validation of a scale - Kukreja, Priyam; Pandey, Jatin (Frontiers in Psychology, 2023)
The corporate world has witnessed an increased narrative about gaslighting at work. Gaslighting is a form of abuse that has transgressed the realms of romantic relationships, to the relationships at work. Despite the growing literature on abuse at work, the conceptualization and measurement of gaslighting at work have received scarce attention. By drawing upon and integrating existing works of literature on harmful leader behaviours, workplace abuse, and workplace mistreatment, the authors have reconceptualized the concept of gaslighting in a new context i.e., work settings, and delineated its dimensions and conceptual boundaries. Furthermore, the paper describes the development and validation of a new 12-item measure of gaslighting in work relationships, the Gaslighting at Work Questionnaire (GWQ). Among 3 different samples (total N= 679) of employees, the study tested the internal consistency, face, and construct validity of the GWQ scale. First, exploratory and confirmatory factor analysis supported a two-dimensional structure of gaslighting at work (trivialization, and affliction). Additionally, the psychometric properties of GWQ were established. Finally, the scale was validated within a nomological net of conceptual relationships using a time-lagged study. The GWQ scale offers new opportunities to understand and measure gaslighting behaviours of a supervisor toward their subordinates in work context.